1999
DOI: 10.1046/j.1440-1835.1999.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Rocky shore turfs dominated by Corallina (Corallinales, Rhodophyta) in northern Japan

Abstract: Three intertidal sites dominated by Corallina turfs were investigated in Hokkaido, Japan. The sites (A, B and C) differed in slope, wave exposure and length of time exposed to air during tidal cycles. Monthly samples were analyzed for frond morphology and other features. Site A, the most wave‐exposed site, was dominated by Corallina sp. X, an unknown species, and sites B and C by Corallina pilulifera Postels et Ruprecht. At the different sites the populations differed in conceptacle abundance, coverage by epip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…In tropical environments, corals are heavily studied in ocean acidiWcation research due to the symbiotic relationship between the photosynthesizing zooxanthellae and the heterotrophic coral (Reynaud et al 2003;Langdon and Atkinson 2005;Krief et al 2010). In temperate environments, calcifying micro-and macroalgae are crucial organisms to investigate because of their high primary production and contribution to global biogeochemical cycles (Thierstein and Young 2004) and importance in providing structural support, refugia, and substrata for inter-and subtidal marine communities (Coull and Wells 1983;Hicks 1986;Akioka et al 1999). Calcifying algae are unique organisms that conduct both photosynthesis and calciWcation-two processes that are intricately linked to DIC (CO 2 , HCO 3 ¡ , CO 3 2¡ ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tropical environments, corals are heavily studied in ocean acidiWcation research due to the symbiotic relationship between the photosynthesizing zooxanthellae and the heterotrophic coral (Reynaud et al 2003;Langdon and Atkinson 2005;Krief et al 2010). In temperate environments, calcifying micro-and macroalgae are crucial organisms to investigate because of their high primary production and contribution to global biogeochemical cycles (Thierstein and Young 2004) and importance in providing structural support, refugia, and substrata for inter-and subtidal marine communities (Coull and Wells 1983;Hicks 1986;Akioka et al 1999). Calcifying algae are unique organisms that conduct both photosynthesis and calciWcation-two processes that are intricately linked to DIC (CO 2 , HCO 3 ¡ , CO 3 2¡ ).…”
Section: Introductionmentioning
confidence: 99%
“…Corallina spp. often form extensive macroalgal turfs that cover large areas of the intertidal and provides substratum, habitat, and refugia for a number of important marine organisms (Coull and Wells 1983;Hicks 1986;Akioka et al 1999;Kelaher 2002Kelaher , 2003. On the rocky coast of the island of Helgoland in the North Sea, C. oYcinalis is abundant and is an important species in the macroalgal community.…”
Section: Introductionmentioning
confidence: 99%
“…The species Corallina pilulifera was identifi ed using anatomical characters, such as the tier number per intergeniculum (12-16) and intergenicular length (0.9-1.2 mm; Baba et al, 1988;Akioka et al, 1999). All eight samples of the coralline algae collected had the same range of tier numbers, which is a key character of C. pilulifera.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological studies alone no longer suffi ce to identify species, as demonstrated by the apparent duplication of descriptions due to geographical, seasonal, and environmental differences. Differences in microhabitat conditions, such as desiccation, epiphyte loading, and the abundance of herbivores, can also alter the morphology (Akioka et al, 1999). Therefore, we used molecular information to complement the physical variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation